Extracting the science : a century of mining research - Brune, Jürgen F. (Society for Mining, Metallurgy, and Exploration, 2010)
An authoritative compilation of research and a description of technological achievements written especially for mine operators, researchers, faculty and students of mining education programs, as well as for regulators and enforcement agencies--indeed, anyone concerned with improving the health and safety of mine workers while enhancing mine productivity. Published to commemorate the 100th anniversary of the United States Bureau of Mines, this volume presents the latest findings from 120 leading mine scientists and operating experts from countries around the world. While paying homage to the past, these authors focus extensively on today's developments and research, providing insights into the many challenges and opportunities facing the industry now and in the years ahead. Includes the latest on preventing catastrophic events, such as fires and major roof or slope failures; providing adequate ventilation to dilute explosive or toxic gases and dusts; preventing hearing loss; providing emergency communication and life support for miners trapped underground; developing training materials and guidelines for improving safety, health, and productivity in mines; and a host of other critical topics. These research papers also cover a spectrum of innovative technical solutions, including computer-controlled mining equipment, remote monitoring of air quality, and virtual reality training systems.